Frequently Asked Questions about Landscape Irrigation for Florida-Friendly Landscaping Ordinances - Michael D. Dukes; Laurie E. Trenholm; Ed Gilman; Chris Martinez; John L. Cisar; Thomas H. Yeager (EDIS)
Revised! ENH-1114, an 8-page fact sheet by Michael D. Dukes, Laurie E. Trenholm, Ed Gilman, Chris J. Martinez, John L. Cisar, and Thomas H. Yeager, was created to help guide local government officials in developing local regulations based on science. It uses a question and answer format to address common concerns related to water, irrigation, and landscapes and their maintenance. Includes references. Published by the UF Department of Environmental Horticulture, January 2009.